Policy Analysis of The Management of Private Islamic Higher Education Institutions in DKI Jakarta and Banten: A Quality and Competitiveness Perspective - Marpudin, Ade; Saleh, Mhd (STAI Publisistik Thawalib Jakarta, 2026)
This study examines the gap in the implementation of management policies for Islamic Higher Education Institutions in DKI Jakarta and Banten, resulting from variations in managerial capacity, infrastructure limitations, and low levels of digitalization, which in turn affect institutional quality and competitiveness. The objectives of this research are to analyze the effectiveness of management policies for Islamic Higher Education Institutions, identify dominant factors influencing quality and competitiveness, and assess the contribution of seven policy variables. The study employs a quantitative method using questionnaires distributed to institutional leaders, with data analyzed through multiple linear regression. The findings indicate that the model explains approximately 77% of the variation in institutional quality and competitiveness and is statistically significant simultaneously. Partially, curriculum, collaboration, quality assurance, and financial management have a positive and significant effect on improving institutional quality and competitiveness. In contrast, facilities and infrastructure have a significant negative effect, indicating structural barriers due to infrastructure limitations. Meanwhile, lecturer quality and technology utilization do not show a significant effect, suggesting that the integration of these aspects into institutional governance has not yet been optimal. The conclusion highlights that governance, collaboration, and quality assurance are the key drivers for improving institutional performance. This study contributes both theoretically and practically to policy development and governance reform, while also offering strategic recommendations for strengthening Islamic higher education through innovation, collaboration, and sustainable digital transformation.